دابەشبوونی جوگرافی پشتێنەكانی ڕووەكی سروشتی لە قەزای شارباژێڕ بۆ ساڵی (2020) (به‌ به‌كارهێنانی چاودێری دوور وسيستمى زانیارییه‌ جوگرافییه‌كان: RS&GIS) - ئەمین, هاوڕێ یاسین محمد; محمد, ئاراز خلیل (Sulaimani Journal for Humanities, 2022)
researching about environment subjects take an important role in geographical researching،because environment in a general meaning is center of all the living things, it guarantees a healthy life, if we save this environment from trouble, Natural grasses is one of the main constituent of environment cycle system, it has many economical and healthy benefits. It is a living center for many animals and wild birds. Natural plant belts and their separation in terms of area and quantity can benefit us greatly on how each of these belts is used and utilizing and protecting them, especially of belts (Forests and natural pastures), therefore separating and describing each of the natural plant belts is one of the leading characteristics of natural plant research that the researcher must act on. Because the research area (Sharbazher district) is a naturally rich area, so we thought it is necessary within the framework of scientific research relying on descriptive method, and the method of analysis for available data and with the usage of contemporary technology and reliance on the image of the artificial moon, and the use of Remote Sensing and Geographic Information System (RS&GIS), we will separate the natural plant belts in the area for 2020, and reveal the area and rate of each belt at the level of academic administrations and the total area of the district.
Keywords: Environment; Belt; Natural Plant; Sharbazher District